Foxp3-Infiltrating Cellular Expression in Rheumatic Mitral Valve Tissue Lesions (Iraqi Journal of Medical Sciences, 2016)
Background: The Foxp3 gene is exclusive. It found in nTregs and correlates with the suppressive activity of these cells.Objective: To detect Foxp3 expression in infiltrating cells in the rheumatic mitral valve tissue lesions and its correlation with the extent of histopathological abnormalities when considered naturally occurring CD4+CD25+ regulatory T cells (nTregs) as the main expressers for this protein.Methods: Rheumatic mitral valve surgical fragments were taken from a total of 48 Iraqi patients with chronic rheumatic heart disease underwent mitral valve replacement in Ibn Al-Bitar Hospital for Cardiac Surgery-Baghdad-Iraq from October 2006-September 2007. Formalin-fixed paraffin-embedded mitral valve tissue sections were prepared. Foxp3-expressing cells were detected by using immunohistochemical staining technique, and histopathological picture was visualized by using hematoxylin and eosin staining.Results: Our results showed that there were no significant association between Foxp3 expression and the history of acute rheumatic fever (negative or positive), and/or the frequency of attacks (single or multiple) among all groups under study (p > 0.05). Also, we found a significant negative correlation between the percentage of Foxp3 strong positive cells and the extent of histopathological abnormalities.Conclusions: There was a negative correlation between Foxp3 strong positive expression and the extent of histopathological abnormalities which reinforce the immunosuppressive role of nTregs against the inflammatory and autoimmune reactions in chronic rheumatic heart disease. Key words: Foxp3, CD4+CD25+ regulatory T cells, mitral valve
Keywords: Foxp3; CD4CD25 regulatory T cells; mitral valve